Language Use In Condolences Among Yorùbá Of Southwest Nigeria - Jelili A. Adeoye; Oluwatoyin Mary Olaiya; Reuben Oluwafemi Ikotun (The Journal of Studies in Language, Culture and Society)
Condolence messages published in the Nigerian national dailies and reasons for the different greetings that were not considered in the previous studies are addressed in this paper. The data for this study included data drawn from the Holy Bible, the Holy Quran, the Nigerian national dailies, books written by some Yoruba authors, the WhatsApp social media, participant observation and tape recording of many events of language use in some homes of people who have at one time or the other suffered bereavement. The findings show that some condolences require elocution, patience, circumlocution, allusive analogies and allusive anecdotes; some attract merry-making and some are mere rhetoric. The import of the paper is that while some condolences are memories tinged with sadness others are either rhetoric or an invitation to wining and dining.